Geolocation of the Brazilian National DNA Database matches as a tool for improving public safety and the promotion of justice. Issue 1 (December 2019) - da Silva Junior, Ronaldo Carneiro; Minervino, Aline Costa; Martinez, Luciano Lamper; Russo, Daniel; Miranda, Daniel Araújo
Abstract: The Brazilian National DNA Database (BNPG) was created in 2013 and has been growing yearly. In the first half of 2019, there was a 70% increase in the number of genetic profiles that joined BNPG. Along with this growth, there was also a 46% increase in the number of matches in the same period. While it is an excellent sign of increasing database effectiveness, this brings challenges to be overcome. One of them is how to monitor and organize the matches so that they become an effective tool for the promotion of justice and public safety. The tracking of the matches that until then was carried out by spreadsheets now needs a more intelligent form of data management. The solution to this question was found through the integration of matches data from the Brazilian National DNA Database with Inteligeo - a geolocation system developed by Brazilian Federal Police. The Inteligeo system was created in 2010. It is a modern and powerful geographical information system, which assists Brazilian forensic experts in the production of technical reports and integrated information management. It is possible to geolocate all kinds of forensic data, such as crime scenes, criminal routes, and correlations between places under investigation. The teams of BNPG and Inteligeo started joint work to implement the project. First, all forensic DNA laboratories and their respective matches were geolocated. Correlations between laboratories and matches distribution maps were created. A protocol was also developed to make it mandatory to register the geographical coordinates of the sites that originated the samples related to matches. The possibilities of this data integration are many, considering that Inteligeo allows integration with external data sources, supports complex geospatial searches and allows the generation of dynamic maps that can be used to instantly assess the general status of the database and view the correlations of individual matches as they occur. At this point, a new tool called Integrated DNA System (SInDNA) is being developed to automate the geolocation of evidence and its relationships. It will allow evidence data to be recorded and geolocated so that when a match occurs, crime scenes can be geographically linked almost automatically.